SEBARAN UNSUR HARA DALAM MENENTUKAN KESUBURAN TANAH UNTUK TANAMAN JAGUNG DI KECAMATAN SIMPANG RAYA KABUPATEN BANGGAI - Katili, Hidayat Arismunandar; Makotos, Novaldi; Djamaluddin, Ismail; Sariani; Rahman, Rival (JTSL (Jurnal Tanah dan Sumberdaya Lahan), 2026)
Maize is a key food commodity underpinning the economy of the Simpang Raya District, yet its yield has fallen to 3.6 tonnes per hectare. Imbalanced or inadequate fertilisation can lead to excessive nutrient uptake by plants, resulting in a decline in soil fertility. This study evaluates soil nutrient availability and fertility status to guide effective soil management aimed at optimising maize growth in Simpang Raya District, Banggai Regency. Using field surveys and kriging interpolation, the spatial distribution of soil nutrients was mapped, followed by comparison with soil fertility standards to determine fertility status. The methods used provided a high level of accuracy and the best estimates for determining soil fertility. Overall, this suite of methods represented a cost-effective and efficient solution for mapping soil fertility across extensive agricultural areas. The research results indicated that the study site had a soil pH of 5.6–6.2 (slightly acidic) and organic carbon (C) of 0.35–1.71%, with an average of 0.99% (very low). Phosphorus (P) content ranged from 7.51–32.01 ppm with an average of 18.09 (moderate), whilst potassium (K) ranged from 8.56–24.20 mg/100g, with an average of 16.55 (low). Cation Exchange Capacity (CEC) was classified as moderate, with an average of 20.93 cmol(+)/kg, ranging from 8.79–25.32 cmol(+)/kg, and Base Saturation (BS) averaged 32.68% (low), ranging from 14.02–58.71%. Overall, soil fertility for maize crops in the Simpang Raya District was classified as low to moderate. Management through liming and the application of organic fertiliser were strongly recommended. To improve soil quality, necessary interventions include liming, land rehabilitation, and the application of bio-fertilisers/biochar to increase organic carbon and base saturation. These measures require support in the form of organic fertiliser subsidies and intensive extension services from the government, particularly for the Simpang Raya District.